Embodied drawings: creating affective spaces through line - Pink, Sidney (My University, 2020)
This paper outlines the artistic practice and research conducted by Sidney Pink as an MFA Studio Art Degree Candidate at Towson University, Maryland. The paper focuses on Pink's development of artistic embodiment and audience embodiment through drawing performances, installations, and soundscapes. Pink describes the importance of collaboration in his practice and his broad artistic influences. Pink analyzes his conceptual ideas through the frameworks of geographer Derek McCormack, the writing of art historian Cornelia H. Butler, and the personal writings of artists Jennie Kiessling and Anne Truitt.
(M.F.A.) -- Towson University, 2018.